COVID‐19 implications for pediatric anesthesia: Lessons learnt and how to prepare for the next pandemic. Issue 2 (5th December 2021) - Afshari, Arash; Disma, Nicola; von Ungern‐Sternberg, Britta S.; Matava, Clyde
Abstract: COVID‐19 is mainly considered an "adult pandemic, " but it also has strong implications for children and consequently for pediatric anesthesia. Despite the lethality of SARS‐CoV‐2 infection being directly correlated with age, children have equally experienced the negative impacts of this pandemic. In fact, the spectrum of COVID‐19 symptoms among children ranges from very mild to those resembling adults, but may also present as a multisystemic inflammatory syndrome. Moreover, the vast majority of children might be affected by asymptomatic or pauci‐symptomatic infection making them the "perfect" carriers for spreading the disease in the community. Beyond the clinical manifestations of SARS‐CoV‐2 infection, the COVID‐19 pandemic may ultimately have catastrophic health and socioeconomic consequences for children and adolescents, which are yet to be defined. The aim of this narrative review is to highlight how COVID‐19 pandemic has affected and changed the pediatric anesthesia practice and which lessons are to be learned in case of a future "pandemic." In particular, the rapid evolution and dissemination of research and clinical findings have forced the scientific community to adapt and alter clinical practice on an unseen and pragmatic manner. Equally, implementation of new platforms, techniques, and devices together with artificial intelligence and large‐scale collaborative efforts may present a giant step for mankind. The valuable lessons of this pandemic will ultimately translate into new treatments modalities for various diseases but will also have the potential for safety improvement and better quality of care. However, this pandemic has revealed the vulnerability and deficiencies of our health‐care system. If not addressed properly, we may end up with a tsunami of burnout and compassionate fatigue among health‐care professionals. Pediatric anesthesia and critical care staff are no exceptions.